2018
DOI: 10.1038/s41377-018-0059-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying single plasmonic nanostructure far-fields with interferometric and polarimetric k-space microscopy

Abstract: Optically resonant nanoantennae are key building blocks for metasurfaces, nanosensors, and nanophotonic light sources due to their ability to control the amplitude, phase, directivity, and polarization of scattered light. Here, we report an experimental technique for the full recovery of all degrees of freedom encoded in the far-field radiated by a single nanostructure using a high-NA Fourier microscope equipped with digital off-axis holography. This method enables full decomposition of antenna-physics in its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…This factor can be corrected for by measurements on trusted references, such as Lambertian emitters, and emitters on air/glass interfaces with highly distinct radiation patterns [131,132]. Also, polarimetric and interferometric back focal plane imaging are possible, but they are potentially hampered by objective birefringence and aberrations [133,134]. Grzela et al [135] demonstrated that the same optical setup can also be used in reverse, i.e.…”
Section: Fourier Imagingmentioning
confidence: 99%
“…This factor can be corrected for by measurements on trusted references, such as Lambertian emitters, and emitters on air/glass interfaces with highly distinct radiation patterns [131,132]. Also, polarimetric and interferometric back focal plane imaging are possible, but they are potentially hampered by objective birefringence and aberrations [133,134]. Grzela et al [135] demonstrated that the same optical setup can also be used in reverse, i.e.…”
Section: Fourier Imagingmentioning
confidence: 99%
“…The uniformity of the polarization orientation is evaluated by extracting the parameter , which provides the local orientation of the polarization ellipse (almost a line, in this case) across the BFP. 45 In Figure 3 m,n both the experimental and the calculated distributions for α( k x , k y ) indicate that the substantially linear polarization follows an axis-symmetric distribution such that the electric field is azimuthally oriented about the beam axis in k x = k y = 0. In this case, the J conservation rule reads as , leading to two fully overlapped beams with SAM σ o = +1 and OAM and σ o = −1 and OAM , respectively (see Figures S6e,f and S7e,f in Supporting Information ).…”
Section: Resultsmentioning
confidence: 85%
“…The distribution of the parameter , shows a substantially linear polarization corresponding to the doughnut ( ≅ 0) (Figures 3i,l). The uniformity of the polarization orientation is evaluated by extracting the parameter , , which provides the local orientation of the polarization ellipse (almost a line, in this case) across the BFP [40]. In Figures 3m,n When the illumination polarization is switched to LHC ( 1) the input SAM and the grating topological charge possess the same sign.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polarization also has been applied for engineering light–matter interactions in waveguide 8,9 and telecommunication 10 . Recently, nanophotonics has opened a new possibility of ultracompact system based on meta-surfaces with a capability of engineering the polarization of light 1113 . Spectral interferometry employing polarization technique has been playing a very important role in characterizing optical properties in various fields 1421 .…”
Section: Introductionmentioning
confidence: 99%